2017
DOI: 10.1002/psp.2080
|View full text |Cite
|
Sign up to set email alerts
|

Geographic variation in parity progression in Australia

Abstract: Australia has moderately high fertility compared to many Western-industrialized countries. The current total fertility rate is around 1.88, but fertility levels are not uniform across the country.There is a distinct geographic pattern with the total fertility rate about 0.5 higher in remote and very remote Australia (2.33) compared to major cities (1.82). In this paper, we examine 2 explanations for this pattern: the compositional hypothesis and the contextual hypothesis. Using event-history methods with joint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…Research from related fields supports the notion that the propensity to have three children is correlated within networks. Three-child families are found to be clustered in space (see Fiori, Graham, and Feng (2014) for Britain, Gray and Evans (2014) for Australia, Bergsvik, Lappegård, and Skardhamar (2016) for Norway), indicating geographic self-selection based on preferences for family size, and/or neighborhood interaction effects for the propensity to have a third child. Similarly, parity-specific analyses reveal that third births also correlate across generations (Cools and Hart 2017), and there is also some evidence that this positive relationship is causal for men (ibid.…”
Section: Mechanisms For Fertility Interaction Effectsmentioning
confidence: 99%
“…Research from related fields supports the notion that the propensity to have three children is correlated within networks. Three-child families are found to be clustered in space (see Fiori, Graham, and Feng (2014) for Britain, Gray and Evans (2014) for Australia, Bergsvik, Lappegård, and Skardhamar (2016) for Norway), indicating geographic self-selection based on preferences for family size, and/or neighborhood interaction effects for the propensity to have a third child. Similarly, parity-specific analyses reveal that third births also correlate across generations (Cools and Hart 2017), and there is also some evidence that this positive relationship is causal for men (ibid.…”
Section: Mechanisms For Fertility Interaction Effectsmentioning
confidence: 99%
“…In 2019 the Total Fertility Rate reached a new low of 1.66. However, this is still higher than many other Western industrialised countries ( Gray & Evans, 2018 ). This trend is assumed to continue, with no recovery of fertility rates assumed in the near future ( ABS, 2018 ).…”
Section: Projection Assumptionsmentioning
confidence: 70%
“…This is mainly because more educated women have their children at older ages. Gray and Evans (2018) also found that socioeconomic conditions had an influence on regional variation in parity progression in Australia. Women living in smaller towns were more likely to have first, second and third births than those in large urban centres, with results indicating that fertility differences were due in part to socioeconomic factors such as urban and regional differences in housing size and affordability.…”
Section: Socioeconomic Factors Associated With Birthsmentioning
confidence: 87%